1997
DOI: 10.1111/1523-1747.ep12340949
|View full text |Cite
|
Sign up to set email alerts
|

A Transglutaminase-Related Antigen Associates with Keratin Filaments in Some Mouse Epidermal Cells

Abstract: A mouse monoclonal IgG, G82, directed against guinea pig liver transglutaminase recognizes a transglutaminase-related antigen that is associated with the keratin intermediate filament network in some primary mouse keratinocytes. The association can be seen at the resolution of individual keratin tonofibrils following fixation and staining for double-label indirect immunofluorescence. Western blots indicate that G82 reacts with two proteins of 95 kDa and 280 kDa, respectively, in extracts of these cells. The 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Both of them could be substrates for TGases, and are constituents of CEs (15, 16). In addition, it has been reported that TGase‐like antigens are associated with keratin filaments in keratinocytes (47). Therefore, Nile red‐stained material within the CEs might be insoluble aggregates composed of keratins, filaggrin, and related substances.…”
Section: Discussionmentioning
confidence: 99%
“…Both of them could be substrates for TGases, and are constituents of CEs (15, 16). In addition, it has been reported that TGase‐like antigens are associated with keratin filaments in keratinocytes (47). Therefore, Nile red‐stained material within the CEs might be insoluble aggregates composed of keratins, filaggrin, and related substances.…”
Section: Discussionmentioning
confidence: 99%
“…Four of these, TGases 1, 2, 3 and ✕ are commonly expressed in epithelia such as the epidermis (Kim et al , 1991;Aeschlimann et al, 1998), although to date only TGases 1 and 3 have proven importance in CE assembly (Candi et al, 1995;Tarcsa et al, 1997;Tarcsa et al, 1998Candi et al, 1999. It has also been proposed that the cross-linking by these enzymes coordinates mechanically the association between the CE and the underlying intracellular keratin intermediate filaments , and perhaps also in the bundling of keratin filaments (Clement et al, 1998). The T G M 1 gene encoding the TGase 1 enzyme is located on chromosome 14q11.2 (Yaminishi et al, 1990;Kim et al, 1992).…”
Section: The Tgasesmentioning
confidence: 99%
“…Therefore, we undertook to examine changes occurring in the skeletal proteins of the lens as the latent TGase becomes activated by Ca 2ϩ in the tissue. This line of research was greatly spurred by our recent finding that a TGase antigen became tightly bound to the IF network in some fibroblasts and keratinocytes (13,14). The present report focuses on the intermediate filament protein vimentin as substrate for the cross-linking enzyme.…”
mentioning
confidence: 93%